2017
DOI: 10.3389/fpls.2017.00893
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis Reveals a Common Host–Pathogen Interaction Pattern in Arabidopsis Immune Responses

Abstract: Many plant pathogens secrete virulence effectors into host cells to target important proteins in host cellular network. However, the dynamic interactions between effectors and host cellular network have not been fully understood. Here, an integrative network analysis was conducted by combining Arabidopsis thaliana protein–protein interaction network, known targets of Pseudomonas syringae and Hyaloperonospora arabidopsidis effectors, and gene expression profiles in the immune response. In particular, we focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…We have reinforced previously described intra- and interspecific convergence of effector targeting with effectors from two new species [11, 12], and showed at the same time that most effector targets are pathogen specific (Fig 2 and S2). Our analyses also supported the previously described tendency of effectors to interact with plant proteins better connected and central in the network [43, 45], and showed that this tendency is even stronger among effector hubs, multi-pathogen targets and bacterial core T3E targets (Table 2 and Fig S5).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have reinforced previously described intra- and interspecific convergence of effector targeting with effectors from two new species [11, 12], and showed at the same time that most effector targets are pathogen specific (Fig 2 and S2). Our analyses also supported the previously described tendency of effectors to interact with plant proteins better connected and central in the network [43, 45], and showed that this tendency is even stronger among effector hubs, multi-pathogen targets and bacterial core T3E targets (Table 2 and Fig S5).…”
Section: Discussionsupporting
confidence: 90%
“…In this work, by compiling our experimental interactomic data on Xcc and Rps and the literature-curated interactions from a wide variety of other pathogen effectors, we extended the notion that effectors tend to privilege interactions with host proteins with higher Ath degree and betweenness centrality [43, 45]. Furthermore, we showed that this tendency is stronger among effector hubs compared to single targets and among multi-pathogen effector targets compared to pathogen-specific targets.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Consequently, network-based protein-protein interaction (PPI) characterize intricate and interwoven relationships that govern cellular functions. Thus, integrating PPI and gene-expression profile provides novel insights into functional interactions amongst deregulated genes 21 25 . This combined approach can provide insights into regulation of cellular processes and identify the interaction architecture and the underlying gene regulatory networks 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids and other substances are used mainly as antioxidants to eliminate reactive oxygen species produced by plants in response to biological stress[ 42]. In P. fortunei, the flavonoids may be used as antioxidants to eliminate the damage caused by excess reactive oxygen, which may play a role in balancing plant defense responses.Pfwus responded to PaWB to regulate morphological variations When invaded by a pathogen, host plants initiate pathogen-associated molecular pattern-triggered immunity and effector-triggered immunity responses, and gene expression patterns of the host plant change[ 43]. Previous studies showed that squamosa promoter binding protein-like 9 SPL9 is the major target of miR156b, and SPL9 by physically interacting with the WUS may regulate axillary bud formation and branching[ 26].…”
mentioning
confidence: 99%